Teacher’s Performance at SD Negeri 1 Tania Makmur, Lempuing Jaya, Ogan Komering Ilir - Ningsih, Dwi Melia (PPSDP International Journal of Education, 2024)
The formulation of the research problem is the performance of teachers at SD Negeri 1 Tania Makmur, Lempuing Jaya District, Ogan Komering Ilir Regency. What factors influence the performance of teachers at SD Negeri 1 Tania Makmur, Lempuing Jaya District, Ogan Komering Ilir Regency? The aim of this research is to describe the performance of teachers at SD Negeri 1 Tania Makmur, Lempuing Jaya District, Ogan Komering Ilir Regency, and to describe the factors that influence the performance of SD Negeri 1 Tania Makmur teachers, Lempuing Jaya District, Ogan Komering Ilir Regency. This research is a field research method, while the type of research applied to interpret research data is descriptive-qualitative. Data collection techniques were carried out through observation, documentation studies, and interviews. The research data was then analyzed by means of triangulation through collecting, presenting, analyzing, and verifying the data. The results of this research show that the performance of SD Negeri 1 Tania Makmur teachers is good. Teachers who work at this school always try to improve their performance in carrying out their duties. Factors that influence the performance of SD Negeri 1 Tania Makmur teachers in Lempuing Jaya District, Ogan Komering Ilir Regency are the educational level of teachers at SD Negeri 1 Tania Makmur, Lempuing Jaya District, Ogan Komering Ilir Regency, and the leadership management of the principal of SD Negeri 1 Tania Makmur, Lempuing Jaya District, Ogan Komering Ilir Regency. as well as the motivation of teachers at SD Negeri 1 Tania Makmur, Lempuing Jaya District, Ogan Komering Ilir Regency.